The comparative economic performance of Chile: 1810 - 1995 - Lüders, Rolf (Estudios de Economía, 2016)
This paper studies the comparative economic record of Chile from immediately after Independence (1820) to the present, as a first step to relate economic policies to that performance in an Economic History to be written. To do the former, three variables were chosen to represent (1) overall behavior (GDP per capita), (2) international performance (exports per capita), and (3) macro-economic discipline (the inflation rate). A sample of 18 countries, to compare Chile's record with was selected, constrained by the availability of information over a long period. These countries were grouped into three categories, ""developed"" countries, Asia and Latin America. Two methods were used for the analysis: (1) a simple comparison of data averages, whose significance was tested, and (2) discriminant analysis, to obtain overall performance comparisons. The three main conclusions are: (1) Chile's GDP per capita did converge towards that of the more developed countries during last Century and also since the late 1970's, while it diverged between 1940 and 1970.